Analysis of pressure-induced deviation of the cricothyroid membrane among pediatric patients - Fujioka, Shoko; Hobo, Yuko; Suga, Yoshifumi; Takano, Koji; Sano, Yuri; Hosaka, Erika; Kimura, Ayano; Abukawa, Yukako (Frontiers in Anesthesiology, 2024)
The study protocol was approved by the Ethics Committee of the Jikei University (ID number: 30-286). Written informed consent was obtained from the patients' parents. This single-institution randomized controlled study was performed in accordance with the guidelines stipulated in the Declaration of Helsinki and Clinical Trials Act established by the Japanese Ministry of Health, Labour, and Welfare.  Trial registration https://center6.umin.ac.jp/cgi-openbin/ctr/ctr_view.cgi?recptno=R000048003The consent for publication was obtained from all study participants.